Maintaining knowledge on curriculum conversation, but through discourse: A dialogue with Gert Biesta - Alice Casimiro Lopes (Pontifícia Universidade Católica de Campinas, 2014)
I present in this paper my dialogue with Gert Biesta about the connections among knowledge, power, curriculum and discourse. I argue that my way of thinking is not a kind of relativism. The absence of a criterion that once and for all justifies a decision making among different possible solutions to a problem - different curriculum options, as well as different ways to educate - is not a reason for the decisions not to be made. I agree with Derrida and Laclau that such decisions are taken in an undecidable terrain. Keywords: Knowledge. Curriculum. Pragmatism.